2007
DOI: 10.1186/1471-2288-7-10
|View full text |Cite
|
Sign up to set email alerts
|

Development of AMSTAR: a measurement tool to assess the methodological quality of systematic reviews

Abstract: Background: Our objective was to develop an instrument to assess the methodological quality of systematic reviews, building upon previous tools, empirical evidence and expert consensus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
2,849
0
112

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,565 publications
(2,970 citation statements)
references
References 26 publications
9
2,849
0
112
Order By: Relevance
“…A Measurement Tool to Assess Systematic Reviews (AMSTAR) was used to measure the quality of the systematic reviews included in the study. 5 The tool uses 11 yes/no items to assess the methodological quality of systematic reviews and has been shown to have good inter-rater agreement, test-retest reliability, and face and construct validity. 6 When assessing an individual study, each positive answer is allocated one point.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…A Measurement Tool to Assess Systematic Reviews (AMSTAR) was used to measure the quality of the systematic reviews included in the study. 5 The tool uses 11 yes/no items to assess the methodological quality of systematic reviews and has been shown to have good inter-rater agreement, test-retest reliability, and face and construct validity. 6 When assessing an individual study, each positive answer is allocated one point.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…This stance reflects the raison d’être of the Cochrane Collaboration, whose use of explicit and auditable quality criteria for undertaking systematic reviews has inspired a weighty methodological handbook,3 numerous tools and checklists4, 5 and structured reporting criteria 6. There is strong emphasis on methodological reproducibility, with the implication that a different review team, using the same search criteria, quality checklists and synthesis tools, should obtain the same result 3…”
Section: Introductionmentioning
confidence: 99%
“…Das QUADAS-Werkzeug wurde bereits in einem vorherigen Editorial vorgestellt [13], nun möchten wir solch ein Werkzeug für die Beurteilung der methodischen Qualität von systematischen Übersichtsarbeiten und Metaanalysen präsentieren. Während die Einhaltung der ebenfalls bereits vorgestellten PRISMACheckliste ein hohes Maß an Berichtsqualität garantiert [4,14], kann mit dem AMSTAR-Werkzeug die methodische Qualität, also die Art und Weise der Durchführung einer systematischen Über-sichtsarbeit, beurteilt werden [15]. Dieses Editorial möchte somit einen weiteren Beitrag dazu leisten, den Leser über die in der Radiologie wichtigen diagnostischen Studien [16 -20] [26].…”
unclassified
“…Dieses Editorial möchte somit einen weiteren Beitrag dazu leisten, den Leser über die in der Radiologie wichtigen diagnostischen Studien [16 -20] [26]. Nicht englischsprachige Artikel wurden übersetzt und von allen Artikeln wurden die Autoren, Institutionen und das Journal unkenntlich gemacht (Verblindung) [15]. Mithilfe einer explorativen Faktorenanalyse wurden diejenigen Hauptkomponenten, die der 37 Punkte umfassenden Checkliste zugrunde liegen, identifiziert und einer Faktorenrotation ausgesetzt [15].…”
unclassified